Transformative Approach in Teaching Large and Mixed Ability Learners in ELT: A Thematic Review - Dhungana, Ankita; Timalsina, Dhurba Prasad (Nepalese Linguistics, 2025)
English Language Teaching (ELT) classroom today are increasingly large, diverse and mixed in learners that poses educators to ensure equitable participation and meaningful engagement of the students. This paper presents a thematic review of transformative approaches that address these challenges in ELT context. Drawing literature published from 2010 to 2023, the review synthesizes studies on learner centered strategies, technology integration, and culturally responsive pedagogy. These approaches are discussed within the theoretical Lens of Paulo Freire’s Critical Pedagogy to highlight how transformative practice grounded in dialogue, empowerment and social justice support equity and participation in ELT classroom. The findings indicate that transformative practices not only support language acquisition but also help teachers address pedagogical issues in the classroom such as accommodating diverse learner capacity, sustaining engagement and promoting equity. The paper contributes insights into how transformative pedagogies can help to foster inclusive and effective ELT practices in increasing large, diverse and mixed ability classroom context.